Examining cross-modal correspondence between ambient color and taste perception in virtual reality - Wu, Zhen; Shi, Rongkai; Li, Ziming; Jiang, Mengqi; Li, Yue; Yu, Lingyun; Liang, Hai-Ning (Frontiers in Virtual Reality, 2022)
This research explores the cross-modal correspondence effect of ambient color on people’s taste perception in virtual reality (VR). To this end, we designed and conducted two experiments to investigate whether and how taste-congruent ambient colors in VR influence taste perception measured by four aspects: (1) taste ratings of a neutral drink; (2) taste association with virtual environments (VEs); (3) associated scenarios when immersed in these VEs, and (4) people's liking of these VEs. In Experiment 1, participants adjusted the ambient light with different cross-modal-related colors in the immersive VE and reported their scaling of VRSQ. Comfortable light intensity for each ambient color was obtained and we found that the ambient colors of brown, grey, and white are less comfortable than other colors. In Experiment 2, participants tasted black tea (as the neutral drink), after being exposed to eight different VEs with different ambient colors. Results showed that pink ambient color significantly increased the sweetness ratings. Differences in the color-taste associations and environment liking were also observed in the ambient color conditions. Our results provide new insights into the cross-modal correspondence effect on ambient color and taste perception not found in prior work in VR scenarios.